SOSIALISASI TIPS DAN TRIK MENYUSUN KARYA TULIS ILMIAH - Sutrisno Sutrisno; made irma lestari (Jurnal Abdi Mandala, 2022)
The purpose of this activity is to provide understanding to final year students about writing scientific articles from theses and theses for students and how to publish them in accredited and unaccredited national journals as a condition for attending the final trial or graduation requirements. This activity is also a means to motivate students to write quality scientific articles from the results of theses and theses. The method of implementing this Community Service (PKM) activity uses the lecture and demonstration method. This activity was carried out through Zoom Meetings and Live Streaming YouTube. This activity involved 2 lecturers of the Wiyatamandala School of Economics, namely Mrs. Made Irma Lestari S.E, M.Acc and Mr. Drs. Sutrisno M.M. The number of participants involved in this community service activity (PKM) are dozens of participants consisting of final year students of the Wiyatamandala School of Economics in the final semester who will face a thesis trial as well as various other students from universities and colleges in Jakarta and its surroundings. The topic of the first material is "Systematics for Writing Scientific Articles". In this session, it is explained about how to write scientific articles so that they can be published in scientific journals as well as providing examples of scientific articles from theses and theses that have been published in student scientific journals and national journals. The topic of the second material is "Ethics and Rules for Writing Scientific Papers". In this session, it is explained about ethical procedures such as citing theoretical references and other general rules in writing scientific papers. This activity is expected to foster enthusiasm in the participants because of the positive response from the participants to the implementation of the training and many enthusiastic participants asking questions either in the Zoom Chat Room or YouTube Live Chat related to the topic of the activity.